Analysis of the natively unstructured RNA/protein-recognition core in the Escherichia coli RNA degradosome and its interactions with regulatory RNA/Hfq complexes. Issue 1 (9th November 2017) - Bruce, Heather A; Du, Dijun; Matak-Vinkovic, Dijana; Bandyra, Katarzyna J; Broadhurst, R William; Martin, Esther; Sobott, Frank; Shkumatov, Alexander V; Luisi, Ben F
Abstract: The RNA degradosome is a multi-enzyme assembly that plays a central role in the RNA metabolism of Escherichia coli and numerous other bacterial species including pathogens. At the core of the assembly is the endoribonuclease RNase E, one of the largest E. coli proteins and also one that bears the greatest region predicted to be natively unstructured. This extensive unstructured region, situated in the C-terminal half of RNase E, is punctuated with conserved short linear motifs that recruit partner proteins, direct RNA interactions, and enable association with the cytoplasmic membrane. We have structurally characterized a subassembly of the degradosome–comprising a 248-residue segment of the natively unstructured part of RNase E, the DEAD-box helicase RhlB and the glycolytic enzyme enolase, and provide evidence that it serves as a flexible recognition centre that can co-recruit small regulatory RNA and the RNA chaperone Hfq. Our results support a model in which the degradosome captures substrates and regulatory RNAs through the recognition centre, facilitates pairing to cognate transcripts and presents the target to the ribonuclease active sites of the greater assembly for cooperative degradation or processing.